Knee Spine Syndrome Mechanism in Knee Osteoarthritis: Review Article - I Made Buda Kurniantara; Gusti Ayu Alit Triwahyuni (Universitas Udayana dan Diaspora Taipei Medical University, 2020)
Introduction: Osteoarthritis (OA) is the most common arthritis and one of the main causes of disability. This injury can occur in any joint, but the most common OA occurrence globally, especially in Indonesia, is Knee OA (KOA). Damage caused by KOA's degenerative process affects the knee and affects the surrounding structures, such as the lumbar vertebra, which increases symptoms of low back pain (LBP). The occurrence of symptoms of LBP is thought to be caused by knee spine syndrome, which is a condition reduced lumbar lordosis angle due to the degenerative phase of KOA. the mechanism of this syndrome has not yet been discussed in detail, so further discussion is needed in the future. Methods: We searched articles using a list of keywords, including